2014
DOI: 10.4236/ajcc.2014.31001
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Trends of Daily Heavy Rainfall Events over Niger River Basin Development Authority Area in Nigeria

Abstract: Using 70 years of daily rainfall records in eight stations, an analysis of variability and trends of daily heavy rainfall events over Niger River Basin Development Authority Area was carried out by using Standardized Anomaly Index and Spearman Rank Correlation Coefficient. Significant temporal variability on interannual and decadal time-scales was observed in the frequency of heavy rainfall events and annual heavy rainfall amount. Both the annual heavy rainfall amount and frequency of heavy rainfall events dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…New noted a wetter condition in the Sahel in the 1990s which continued into the beginning of the 21 st century [12]. Also Babatolu reported an increasing trend in heavy rainfall in U&LNRBDA [14].…”
Section: Important Food Crops Produced In the Study Areamentioning
confidence: 99%
“…New noted a wetter condition in the Sahel in the 1990s which continued into the beginning of the 21 st century [12]. Also Babatolu reported an increasing trend in heavy rainfall in U&LNRBDA [14].…”
Section: Important Food Crops Produced In the Study Areamentioning
confidence: 99%
“…Nevertheless, the rise in water demand which outweighs supply in the dryer areas during the dry season is premised on rapid population growth coupled with increasing urbanization as a result of economic growth which many African countries are faced with. Nigeria"s water resources are under severe siege due to deteriorating water quantity and quality (Babatolu et al, 2014). Larger outputs in rice production and other agricultural produces in the Sub-Sahara Africa (SSA) come from the Northern region of Nigeria.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Cheung et al (2008) found a significant decline in June to September rainfall for the Baro-Akobo, Omo-Ghibe, Rift Valley, and Southern Blue Nile watersheds located in the southwestern and central parts of Ethiopia but there is no significant negative trend in annual trend in Ethiopia. Babatolu et al (2014) studied the variability and trends of heavy rainfall over Niger River Basin. They found apparent evidence of a temporal change in heavy rainfall events in the last three decades in Niger.…”
Section: Introductionmentioning
confidence: 99%